Differences in onset timing of muscle activities during two types of jump landings - Sasaki, R.; Urabe, Y. (ISBS - Conference Proceedings Archive (Konstanz), 2012)
The purpose of this study was to determine the differences in onset timing of muscle activities between single leg landings and double leg landings. Healthy male college students participated in this study. All subjects performed two types of jump landings, single leg and double leg. The muscle activation during jump landings was measured using electromyography. Muscle activity onset occurred earlier during the single leg landing than during double leg landing, however, there were no significant differences between the onset of the quadriceps femoris muscles` activities and that of the hamstring muscles` activities. Results showed that the earlier muscle activation during motions such as the single leg landing may contribute to decreasing the impact to the joint.